Borderlands [videorecording (DVD)] - Roth, Eli, 1972-; Crombie, Joe; Stoffers, Rogier; Jablonsky, Steve; Blanchett, Cate, 1969-; Hart, Kevin, 1979-; Ramírez, Édgar, 1977-; Greenblatt, Ariana, 2007-; Munteanu, Florian; Gavankar, Janina, 1980-; Gershon, Gina; Curtis, Jamie Lee, 1958-; et al. (Lionsgate, 2024)
Lilith, an infamous bounty hunter with a mysterious past, reluctantly returns to her home, Pandora, the most chaotic planet in the galaxy. Her mission is to find the missing daughter of Atlas, the universe's most powerful SOB. Lilith forms an unexpected alliance with a ragtag team of misfits - Roland, a seasoned mercenary on a mission; Tiny Tina, a feral preteen demolitionist; Krieg, Tina's musclebound protector; Tannis, the oddball scientist who's seen it all; and Claptrap, a wiseass robot. Together, these unlikely heroes must battle an alien species and dangerous bandits to uncover one of Pandora's most explosive secrets. The fate of the universe could be in their hands; but they'll be fighting for something more: each other.